Boy of chaotic making - Holmberg, Charlie N., 1988- (Holmberg, Charlie N., 1988- Whimbrel House, 2024)
Merritt Fernsby's life has changed considerably since he inherited Whimbrel House. He's engaged to Hulda Larkin, who opened his eyes to the uncanny. And he's grown quite protective of his uncle Owein -- several generations, and iterations, removed. Owein is presently inhabiting the body of a mixed-breed terrier when Merritt receives a missive from none other than Alexandrina Victoria, the Queen of England: I am interested in your dog. It's the queen's duty to the peerage to keep British wizardry empowered. Her offer: England will find a human vessel for Owein, marry him into the royal family, and add this remarkable soul-shifter to its lineage. For Owein, a boy trapped in the body of a pup, it's a dream come true. How can Merritt refuse? However, once they are in London and in consortium with a necromancer, the situation doesn't feel right, both with their hosts and the house they inhabit. Owein is having nightmares. And Hulda's premonitions warn of danger in Merritt's future. Clearly, someone does not want them in town. But after two hundred years of being cursed to drift, Owein is determined to chart his own destiny. He's ready to defy whatever chaos is coming. After all, Owein is the master of chaos, and with Merritt and Hulda's love and magical support, he can overcome anything.---Publisher description.